State Response
Given input sequence x(0), x(1), x(2), …, the state response is
s(0) = initialState = s0 (say)
s(1) = as0 + bx(0)
s(2) = as(1) + bx(1) = a2 s0 + abx(0) + bx(1)
s(3) = as(2) + bx(2) = a3 s0 + a2bx(0) + abx(1) + bx(2)
…
So ∀ n 3 0
s(n) = an s0 + ∑ (m = 0 to n-1) a n- 1 - m bx(m) .
The state response can be decomposed into the sum of the zero input state response (response if input = 0)
an s0
and the zero state state response (the state response if initial state s0 = 0)
∑ (m = 0 to n) a n - 1 - m bx(m)